2020
DOI: 10.7759/cureus.7869
|View full text |Cite
|
Sign up to set email alerts
|

Basal Ganglia Involvement and Altered Mental Status: A Unique Neurological Manifestation of Coronavirus Disease 2019

Abstract: Like other respiratory viruses, severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) may enter the central nervous system (CNS) via the hematogenous or neuronal path. However, neurological complications of coronavirus disease 2019 (COVID-19) have not been reported frequently. Encephalopathy has been described as a presenting symptom or complication of COVID-19 in some reports. We report a case of a 54-year-old patient who presented with unique clinical characteristics and imaging with brain basal gangl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
51
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 14 publications
1
51
0
1
Order By: Relevance
“…23 patients had ICH and 24 patients had ischemic stroke. Among the COVID-19 patients with ICH, 19 (69.6%) patients had lobar hemorrhage, which was significantly high compared to the number of patients with non-lobar hemorrhage (7 [30.4%]) Retrospective Iran Behzadnia et al [ 112 ] Hemorrhagic lesions and white matter microhemorrhages in 30% and 24% of 37 COVID-19 patients presenting with neurological manifestations with relevant abnormal brain MRI, respectively Retrospective France Kremer et al [ 30 ] Bilateral basal ganglia hemorrhage Case report Iran Haddai et al (2020) [ 113 ] Immune thrombocytopenic purpura—SAH Case report France Zulfiqar et al (2020) [ 114 ] Vasculitis Case report France Hanafi et al (2020) [ 115 ] Cerebral venous sinus thrombosis Case report UK Hughes et al (2020) [ 116 ] Cerebral venous thrombosis Case report USA Klein et al [ 117 ] Venus thromboembolism was seen in 36% and ischemic stroke in 2.5% of 388 patients Retrospective Italy Lodigiani et al [ 118 ] Silent hypoxemia Attributable to the brain infection and subsequent dysfunction of breathe controlling centers in cortical regions rather than subcortical structures and the brain stem Commentary NA Coen et al (2020) [ 120 ] White matter and globus pallidum inflammatory lesions CT scan of the brain demonstrated hypodense lesions involving supratentorial white matter and pallidum bilaterally. MRI showed bilateral but asymmetrical lesions with periventricular and deep white matter involvement Case report France Brun et al (2020) [ 147 ] Neuroleptic malignant syndrome Haloperidol decanoate use 3 weeks prior to admission Case report USA Kajani et al (2020) [ 127 ] Steroid responsiv...…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…23 patients had ICH and 24 patients had ischemic stroke. Among the COVID-19 patients with ICH, 19 (69.6%) patients had lobar hemorrhage, which was significantly high compared to the number of patients with non-lobar hemorrhage (7 [30.4%]) Retrospective Iran Behzadnia et al [ 112 ] Hemorrhagic lesions and white matter microhemorrhages in 30% and 24% of 37 COVID-19 patients presenting with neurological manifestations with relevant abnormal brain MRI, respectively Retrospective France Kremer et al [ 30 ] Bilateral basal ganglia hemorrhage Case report Iran Haddai et al (2020) [ 113 ] Immune thrombocytopenic purpura—SAH Case report France Zulfiqar et al (2020) [ 114 ] Vasculitis Case report France Hanafi et al (2020) [ 115 ] Cerebral venous sinus thrombosis Case report UK Hughes et al (2020) [ 116 ] Cerebral venous thrombosis Case report USA Klein et al [ 117 ] Venus thromboembolism was seen in 36% and ischemic stroke in 2.5% of 388 patients Retrospective Italy Lodigiani et al [ 118 ] Silent hypoxemia Attributable to the brain infection and subsequent dysfunction of breathe controlling centers in cortical regions rather than subcortical structures and the brain stem Commentary NA Coen et al (2020) [ 120 ] White matter and globus pallidum inflammatory lesions CT scan of the brain demonstrated hypodense lesions involving supratentorial white matter and pallidum bilaterally. MRI showed bilateral but asymmetrical lesions with periventricular and deep white matter involvement Case report France Brun et al (2020) [ 147 ] Neuroleptic malignant syndrome Haloperidol decanoate use 3 weeks prior to admission Case report USA Kajani et al (2020) [ 127 ] Steroid responsiv...…”
Section: Discussionmentioning
confidence: 99%
“…In the study conducted by Kremer et al [ 30 ], hemorrhagic lesions and isolated white matter microhemorrhages were observed in 11 (30%) and 9 (24%) COVID-19 patients, respectively, while 20 patients (54%) had ICH with a more severe clinical presentation. Haddai et al [ 113 ] reported a 54-year-old COVID-19 female patient with bilateral basal ganglia hemorrhage. Zulfiqar et al [ 114 ] reported immune thrombocytopenic purpura in a patient with COVID-19 who later showed SAH in his right frontal lobe.…”
Section: Cns Manifestations Associated With Covid-19mentioning
confidence: 99%
“…Subarachnoid hemorrhage was also reported by Craen and colleagues [26] as a complication of COVID-19 in a 66-year-old woman with a past medical history of diabetes, hypertension and hyperlipidemia. A rare case of bilateral basal ganglia hemorrhage was detected by Haddadi and colleagues [38] in a 54-year-old woman who had contracted SARS-CoV-2 infection and with a past medical history of diabetes, hypertension, lumbar spinal laminectomy and fusion surgery. Microhemorrhages were revealed by MRI in corpus callosum, basal ganglia and brainstem in a 69-year-old COVID-19 patient with a history of hypertension, chronic kidney disease, and hypothyroidism reported by Shoskes and colleagues [55].…”
Section: Effects Of Sars-cov-2 On Cnsmentioning
confidence: 95%
“…There has been 1 previous case reported in the literature of bilateral basal ganglia involvement in a patient with presumed COVID-19 infection; however, that patient's nasopharyngeal SARS-CoV-2 polymerase chain reaction was negative (Table). 4 Poyiadji et al 7 reported a case of a woman with COVID-19 who was found to have hemorrhagic rimenhancing lesions within the bilateral thalami and medial temporal lobes.…”
Section: Discussionmentioning
confidence: 99%
“…1 Neurologic manifestations may occur in up to 50% of patients with coronavirus disease 2019 (COVID-19) and may include encephalopathy, anosmia, ageusia, headache, dizziness, seizure, stroke, increased intracranial pressure, SARS-CoV-2 meningitis, and necrotizing encephalitis. [2][3][4] There have been cases of ischemic and hemorrhage strokes in patients with COVID-19. 5 Bilateral basal ganglia hemorrhages per se are exceedingly rare, with 1 study indicating less than 30 reported cases worldwide.…”
mentioning
confidence: 99%